2014
DOI: 10.1155/2014/941341
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hexavalent Chromium by Viable Cells of Chromium Resistant Bacteria Isolated from Chromite Mining Environment

Abstract: Environmental contamination of hexavalent chromium [Cr(VI)] is of serious concern for its toxicity as well as mutagenic and carcinogenic effects. Bacterial chromate reduction is a cost-effective technology for detoxification as well as removal of Cr(VI) from polluted environment. Chromium resistant and reducing bacteria, belonging to Arthrobacter, Pseudomonas, and Corynebacterium isolated from chromite mine overburden and seepage samples of Orissa, India, were found to tolerate 12-18 mM Cr(VI) during growth. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
2
6
0
1
Order By: Relevance
“…It was possible to observe a decrease in the rate of reduction of chromium, although an increase in the number of microorganisms was presented (Figure 3). Similar results were observed in the work of Dey et al 30 who tested four different bacterial strains, showing that the highest rate of reduction was observed in the first hours of the assay. In contrast, in the assays performed with IW a significantly lower growth was showed than the one observed in LB.…”
Section: Discussionsupporting
confidence: 90%
“…It was possible to observe a decrease in the rate of reduction of chromium, although an increase in the number of microorganisms was presented (Figure 3). Similar results were observed in the work of Dey et al 30 who tested four different bacterial strains, showing that the highest rate of reduction was observed in the first hours of the assay. In contrast, in the assays performed with IW a significantly lower growth was showed than the one observed in LB.…”
Section: Discussionsupporting
confidence: 90%
“…The presented data shows that with an increase in the Cr(VI) content in the LB medium, decrease of the number of Cr(VI) [35] reported that only 12% of bacteria were capable of growth at 1000 ppm Cr(VI) were also detected at 500 ppm. However, Dey et al [36] found that the rate of bacterial growth reduction was about 50% at a Cr(VI) concentration of 2 mM compared to the control, which is in agreement with this study.…”
Section: Microbiological Diversity and Cr(vi) Tolerancesupporting
confidence: 93%
“…Similar behaviors have been reported with Arthrobacter sp. SUK 1201 ( Dey et al, 2014 ), Pseudomonas CRB5 ( McLean et al, 2000 ), and Bacillus sphaericus AND 303 ( Pal and Paul, 2004 ). Simultaneously, the higher cell density induced faster Heme red recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial Cr(VI) reduction can be influenced by different environmental factors, such as Cr(VI) concentration, temperature, bacterial cell density, electron donor, pH, oxygen, and the presence of other metal ions ( Wang and Xiao, 1995 ; Dey et al, 2014 ). Past studies ( Wang and Xiao, 1995 ; Zakaria et al, 2007 ; Dey et al, 2014 ) mainly focused on effects of incubation factors on the apparent Cr(VI) reduction and rarely investigated the effects of incubation factors on the redox status of c -Cyts in the OM of DMRB, which play a key role in microbial Cr(VI) reduction. In situ spectral kinetics of Cr(VI) reduction by c -Cyts in live cells under different environmental conditions should provide a more fundamental understanding of the molecular-level mechanisms.…”
Section: Introductionmentioning
confidence: 99%